Ready for translation: non-invasive auricular vagus nerve stimulation inhibits psychophysiological indices of stimulus-specific fear and facilitates responding to repeated exposure in phobic individuals - Christoph Szeska; Kai Klepzig; Alfons O. Hamm; Mathias Weymar (Translational Psychiatry)
Abstract Recent laboratory research showed that vagus nerve stimulation promotes fear extinction, the inhibitory core mechanism of exposure treatment, presumably via activation of the noradrenergic brain system. However, a translation of this stimulation technique to clinical practice is lacking. We therefore investigated the potential of vagal stimulation to inhibit excessive fear responses and facilitate responding to in-vivo and laboratory exposure in individuals with specific phobia. Spider-phobic participants were subjected to three standardized in-vivo exposures towards a living tarantula, complemented by an exposure in vitro (between exposure in vivo I and II). Transcutaneous auricular vagus nerve stimulation (taVNS) was applied during in-vitro exposure, presenting pictures of the exposed tarantula, other spiders and neutral tools in the laboratory. Fear was assessed by self-reports and behavioral avoidance (in-vivo exposures), and amygdala-mediated autonomic and behavioral fear components (exposure in vitro). Vagal stimulation facilitated the reduction of behavioral avoidance across repeated in-vivo exposures. During laboratory exposure, taVNS inhibited fear tachycardia and corrugator muscle activity specifically in response to pictures of the previously exposed tarantula – an effect that became stronger with increasing stimulation duration. Psychophysiological indices of noradrenergic transmission in the basolateral amygdala were elevated during taVNS and correlated to subsequent attenuation of behavioral avoidance. Our results suggest, that taVNS exerts stimulus-specific and dose-dependent inhibition of multiple automatic response components of excessive fear, highlighting taVNS as a valuable adjunct to exposure-based treatment. A translational mechanism of action is supported, proposing that taVNS exhibits its effects by noradrenergic activation of fear extinction circuitry, particularly targeting the basolateral amygdala.